Audit of Orthopaedic Surgical Documentation. (19th August 2015) - Coughlan, Fionn; Ellanti, Prasad; Ní Fhoghlu, Cliodhna; Moriarity, Andrew; Hogan, Niall
Abstract : Introduction . The Royal College of Surgeons in England published guidelines in 2008 outlining the information that should be documented at each surgery. St. James's Hospital uses a standard operation sheet for all surgical procedures and these were examined to assess documentation standards. Objectives . To retrospectively audit the hand written orthopaedic operative notes according to established guidelines. Methods . A total of 63 operation notes over seven months were audited in terms of date and time of surgery, surgeon, procedure, elective or emergency indication, operative diagnosis, incision details, signature, closure details, tourniquet time, postop instructions, complications, prosthesis, and serial numbers. Results . A consultant performed 71.4% of procedures; however, 85.7% of the operative notes were written by the registrar. The date and time of surgery, name of surgeon, procedure name, and signature were documented in all cases. The operative diagnosis and postoperative instructions were frequently not documented in the designated location. Incision details were included in 81.7% and prosthesis details in only 30% while the tourniquet time was not documented in any. Conclusion . Completion and documentation of operative procedures were excellent in some areas; improvement is needed in documenting tourniquet time, prosthesis and incision details, and the location of operative diagnosis and postoperative instructions.